2007
DOI: 10.1111/j.1600-0897.2007.00482.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Responses of Murine Vaginal and Uterine Epithelial Cells Prior to and Following Herpes Simplex Virus Type 2 (HSV‐2) Infection

Abstract: This data shows that ECs from the upper and lower reproductive tract have different cytokine secretion profiles and respond differentially to infection. HSV-2 may be able to suppress epithelial cytokine secretion as a strategy to evade host immune system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Transfer of maternally produced antibodies and cytokines across the placenta and/or exposure of the fetus to inflammatory molecules produced by the placenta and decidua in relation to viral shedding may lead to fetal brain inflammation. HSV-2 shedding has been reported to occur simultaneously in distinct regions of the genital tract, independently of lesions linked to more localized inflammation ( 46 48 ), and is associated with increased levels of interleukin 6 (IL-6) and tumor necrosis factor alpha (TNF-α) ( 49 , 50 ). There is evidence that these cytokines can enter fetal circulation ( 51 54 ), cross the blood-brain barrier (BBB), and stimulate production of inflammatory cytokines by microglial cells and astrocytes in fetal brain, further increasing the permeability of the BBB and damaging the developing white matter ( 55 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Transfer of maternally produced antibodies and cytokines across the placenta and/or exposure of the fetus to inflammatory molecules produced by the placenta and decidua in relation to viral shedding may lead to fetal brain inflammation. HSV-2 shedding has been reported to occur simultaneously in distinct regions of the genital tract, independently of lesions linked to more localized inflammation ( 46 48 ), and is associated with increased levels of interleukin 6 (IL-6) and tumor necrosis factor alpha (TNF-α) ( 49 , 50 ). There is evidence that these cytokines can enter fetal circulation ( 51 54 ), cross the blood-brain barrier (BBB), and stimulate production of inflammatory cytokines by microglial cells and astrocytes in fetal brain, further increasing the permeability of the BBB and damaging the developing white matter ( 55 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that HSV [40] and HIV [36] are associated with an increased risk of BV, but human papillomavirus (HPV) is not similarly associated [41]. After infection with HSV, cultured uterine epithelial cells secreted lower IL-6 and MCP-1 levels [42], and cervical epithelial cells secreted less SLPI [43]. HIV has well described effects on CD4 + T cells and adaptive immunity, but has also been associated with alterations in innate mucosal immunity.…”
Section: Viral Coinfectionsmentioning
confidence: 99%
“…CXCL1 is produced by epithelial cells within the genital mucosa (17) and is rapidly secreted following HSV-2 infection (59). Like CXCL1, CCL2 is also generated rapidly in response to HSV-2 (59) and is associated with inflammation and tissue pathology (12,31,43).…”
Section: Discussionmentioning
confidence: 99%